Improving selective football performance skills: In the case of University of Gondar third year sport science football elective students of 2022. - Abebe, Yibeltal (INTERNATIONAL JOURNAL OF RESEARCH PEDAGOGY AND TECHNOLOGY IN EDUCATION AND MOVEMENT SCIENCES, 2023)
The aim of study is to improve football skills such as passing, dribbling and shooting of third year football elective students within eight weeks mixed football training program. 12 male and 6 female totally 18 football elective third year sport science students of Gondar University were participated in the study. All participants were selected by comprehensive sampling method. Descriptive statistics (mean and standard deviation) and inferential statistics (Paired Sample T test) were used for data analysis. The mean score (42.17 for dribbling skill, 74.47 for passing skill and 17.94 for shooting skill) from pretest revealed that the performance mean score of dribbling, passing and shooting skills of all participants were low. After eight weeks training implemented, the participant students improved their skills of dribbling, passing and shooting. As findings of this study from posttest after intervention depicted that the performance mean score (31.28 for dribbling skill, 55.72 for passing skill and 32.56 for shooting skill); there were significant difference between pretest and posttest mean score of dribbling , passing and shooting skills. Because of the p value of the three football skills were .00 which less than the p value of 0.05; this shows there were highly significant difference between means of the pretest and posttest of the above three football skills. The intervention was very effective and successful in the improvement of participants dribbling, passing and shooting skills.